2020
DOI: 10.1038/s41561-020-0578-1
|View full text |Cite
|
Sign up to set email alerts
|

The Earth’s core as a reservoir of water

Abstract: Current estimates of the budget and distribution of water in the Earth have large uncertainties, most of which come from the lack of information about the deep Earth. Recent studies suggest that the Earth could have gained a considerable amount of water during the early stages of Earth's evolution from the hydrogen-rich solar nebula, and that a large amount of the water in the Earth may have partitioned into the core. Here, we calculate the partitioning of water between iron and silicate melts at 20-135 gigapa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
58
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 38 publications
7
58
1
Order By: Relevance
“…However, these possibilities are less likely. The water content of the core remains controversial (e.g., Clesi et al., 2018; Hirose et al., 2019; Iizuka‐Oku et al., 2017; Li et al., 2020; Okuchi et al., 1997; Terasaki et al., 2012; Yuan & Steinle‐Neumann, 2020), but it is most likely not decreasing over time, making it an unlikely source of an increase in mantle water. Possible hydrous partial melts in the early mantle would have likely been too buoyant to remain gravitationally stable at depth (Mookherjee et al., 2008) and would have erupted to release their water onto the surface.…”
Section: Resultsmentioning
confidence: 99%
“…However, these possibilities are less likely. The water content of the core remains controversial (e.g., Clesi et al., 2018; Hirose et al., 2019; Iizuka‐Oku et al., 2017; Li et al., 2020; Okuchi et al., 1997; Terasaki et al., 2012; Yuan & Steinle‐Neumann, 2020), but it is most likely not decreasing over time, making it an unlikely source of an increase in mantle water. Possible hydrous partial melts in the early mantle would have likely been too buoyant to remain gravitationally stable at depth (Mookherjee et al., 2008) and would have erupted to release their water onto the surface.…”
Section: Resultsmentioning
confidence: 99%
“…Liu et al (2017) elucidated that the sound velocity in FeO 2 H x can explain the seismic structure of ultralow velocity zones (ULVZs), which represent dense domains that are characterized by variable thicknesses in the range 5–40 km at the base of the lower mantle (Garnero & Helmberger, 1998; McNamara et al, 2010). Moreover, a recent theoretical study revealed that water at the base of the mantle would partition strongly into the core, and the ULVZs would be dry (Li et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Naively we might expect the temperature drop from 5300 K to 4800 K to produce a similar O(100) km change in stable layer thickness to that found for our calculations at 5900 K and 5300 K; however, this assumes that partitioning of H and its effect on thermal conductivity are similar to that of O, for which there is as yet no evidence. Furthermore, Li et al (2020) suggest from partitioning calculations that the hydrogen concentrations considered by Umemoto and Hirose (2020) are too large to be compatible with the estimated present-day mantle water content. We therefore conclude that our calculations provide plausible uncertainties on the composition-dependence of stable layer thickness given the presently available information.…”
Section: Discussionmentioning
confidence: 96%